2011
DOI: 10.1111/j.1095-8649.2011.03090.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic evaluation of Rutilus spp. from Skadar, Ohrid and Prespa Lakes supports revision of endemic as well as taxonomic status of several taxa

Abstract: One mtDNA gene (cytochrome b), one nuclear DNA fragment, five microsatellites and a suite of morphological characters were evaluated in samples of Rutilus spp. from Skadar, Ohrid and Prespa Lakes. Both genetic and phenotypic data supported two sympatric taxa in Lake Skadar, whereby Prespa and Ohrid Lakes revealed only a single taxon each. One of the taxa from Lake Skadar was similar to samples from Lake Prespa, whereas the second taxon was the most divergent in the data set. The estimated time to the most rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
7
0
5
Order By: Relevance
“…Study on perch (Svanbäck & Eklöv, 2002;2006) indicated that perch caught in the littoral habitat, independent of size, had a deeper body, larger head, and mouth and longer fins than perch caught in the pelagic zone. Bearing in mind that the Lake Skadar is generally shallow and subject to large surface area fluctuations obtained results are in correlation with general littoral distribution of R. prespensis (Milošević et al, 2011).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Study on perch (Svanbäck & Eklöv, 2002;2006) indicated that perch caught in the littoral habitat, independent of size, had a deeper body, larger head, and mouth and longer fins than perch caught in the pelagic zone. Bearing in mind that the Lake Skadar is generally shallow and subject to large surface area fluctuations obtained results are in correlation with general littoral distribution of R. prespensis (Milošević et al, 2011).…”
Section: Discussionsupporting
confidence: 67%
“…from the extant ancient Balkan lakes (Prespa, Ohrid and Skadar) share a relatively recent (within the Pleistocene) common ancestry. This ancestral haplotype was found in Lake Prespa and in Lake Skadar individuals of R. prespensis (Milošević et al, 2011). Genetic variation for a fixed phenotype has been hypothesized in stable environments (Smith, 1993).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…1). This considerably more structured phylogeographic 200 pattern than previously proposed may explain why taxonomists 201 have been unable to clearly distinguish putative P. lumarieul from 202 P. phoxinus (Bianco, 2014 in morphological (Talevski et al, 2009;Bogutskaya et al, 2012) and 216 molecular studies (Milosević et al, 2011;Tsoumani et al, 2014). 217 Moreover, we found three additional clades along the Adriatic river …”
Section: Tablementioning
confidence: 63%
“…1.2). Rutilus prespensis (Karaman, 1924): ενδημικό της Μικρής και της Μεγάλης Πρέσπας (Crivelli et al 1997, Milosevic et al 2011). Παμβώτιδα (Economidis et al 2000.…”
Section: κατανομή του γένους Rutilus στην ελλάδαunclassified